The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1001/jamainternmed.2022.4333
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia Care for Cataract Surgery in Medicare Beneficiaries

Abstract: ImportanceCataract surgery in the US is routinely performed with anesthesia care, whereas anesthesia care for other elective, low-risk, outpatient procedures is applied more selectively.ObjectiveTo identify predictors of anesthesia care in Medicare beneficiaries undergoing cataract surgery and evaluate anesthesia care for cataract surgery compared with other elective, low-risk, outpatient procedures.Design, Setting, and ParticipantsThis population-based, retrospective observational cohort study included Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…In Reply We thank Drs Nemet and Tuuminen and Dr Dalia and colleagues for their interest in our article. 1 Drs Nemet and Tuuminen's experiences in Finland add to the growing body of literature suggesting that complications after cataract surgery are exceedingly rare, even though anesthesia care for cataract surgery is used much more selectively at their institution than it is in the US. This approach to cataract surgery sedation is also the prevailing practice throughout the UK, 2 as well as at other dedicated eye care centers, 3,4 and has been shown to be safe and acceptable to patients in these settings.…”
Section: Achia Nemet MD Raimo Tuuminen Md Phdmentioning
confidence: 99%
See 3 more Smart Citations
“…In Reply We thank Drs Nemet and Tuuminen and Dr Dalia and colleagues for their interest in our article. 1 Drs Nemet and Tuuminen's experiences in Finland add to the growing body of literature suggesting that complications after cataract surgery are exceedingly rare, even though anesthesia care for cataract surgery is used much more selectively at their institution than it is in the US. This approach to cataract surgery sedation is also the prevailing practice throughout the UK, 2 as well as at other dedicated eye care centers, 3,4 and has been shown to be safe and acceptable to patients in these settings.…”
Section: Achia Nemet MD Raimo Tuuminen Md Phdmentioning
confidence: 99%
“…Lastly, Dr Dalia and colleagues assert that the model results we shared in the online supplement 1 cannot account for all factors that affect the assignment of anesthesia care and/or the risk of developing perioperative complications. We agree that observational studies can only account for measured con- founders.…”
Section: Publishedmentioning
confidence: 99%
See 2 more Smart Citations
“…To the Editor In a recent cohort study by Dr Perumal and colleagues including 36 652 patients who had undergone cataract surgery, the authors observed that despite nearly 90% of the surgical procedures being performed under anesthesia care, systemic perioperative complications were infrequent. Moreover, using anesthesia care was not associated with the complication rate.…”
mentioning
confidence: 99%